Distinct T cell subsets in adipose tissue are associated with obesity. Issue 2 (13th December 2022) - Haugstøyl, Martha E.; Cornillet, Martin; Strand, Kristina; Stiglund, Natalie; Sun, Dan; Lawrence‐Archer, Laurence; Hjellestad, Iren D.; Sparrelid, Ernesto; Busch, Christian; Hjelmesæth, Jøran; Hertel, Jens K.; Ponzetta, Andrea; et al.
Abstract: Adipose tissue inflammation is a driving factor for the development of obesity‐associated metabolic disturbances, and a role of adipose tissue T cells in initiating the pro‐inflammatory signaling is emerging. However, data on human adipose tissue T cells in obesity are limited, reflected by the lack of phenotypic markers to define tissue‐resident T cell subsets. In this study, we performed a deep characterization of T cells in blood and adipose tissue depots using multicolor flow cytometry and RNA sequencing. We identified distinct subsets of T cells associated with obesity expressing the activation markers, CD26 and CCR5, and obesity‐specific genes that are potentially engaged in activating pro‐inflammatory pathway, including ceramide signaling, autophagy, and IL‐6 signaling. These findings increase our knowledge on the heterogeneity of T cells in adipose tissue and on subsets that may play a role in obesity‐related pathogenesis. Abstract : By an in‐depth profiling of human adipose tissue we identified distinct subsets of T cells associated with obesity. The findings increase of knowledge on heterogeneity of T cells in adipose tissue and on subsets that may play a role in obesity‐related pathogenesis.